miR-215 Enhances HCV Replication by Targeting TRIM22 and Inactivating NF-κB Signaling - Tian, Hui (Yonsei Med J, 2018)
PURPOSE: Hepatitis C virus (HCV) infection is a major cause of liver disease. Several miRNAs have been found to be associated with HCV infection. This study aimed to investigate the functional roles and possible molecular mechanisms of miR-215 in HCV replication. MATERIALS AND METHODS: The expression levels of miR-215 and TRIM22 were detected by quantitative real-time PCR (qRT-PCR) and western blot analysis in Con1b subgenomic genotype 1b HCV replicon cells (Con1b cells) and JFH1 full genome infecting Huh7.5.1 cells (Huh7.5.1 cells). HCV RNA levels were measured by qRT-PCR. The protein levels of NS3, NS5A, p65 subunit of NF-κB (p65), and phosphorylated p65 (p-p65) were determined by western blot analysis. The relationship between miR-215 and TRIM22 were explored by target prediction and luciferase reporter analysis. RESULTS: miR-215 overexpression enhanced HCV replication in Con1b cells, while miR-215 knockdown suppressed HCV replication in Huh7.5.1 cells. TRIM22 was confirmed to be a direct target of miR-215. TRIM22 upregulation resulted in a decline in HCV replication, while TRIM22 inhibition led to enhancement of HCV replication. Additionally, exogenous expression of TRIM22 reversed the facilitating effect of miR-215 on HCV replication, while TRIM22 downregulation counteracted the inhibitory effect of miR-215 knockdown on HCV replication. Furthermore, miR-215 targeted TRIM22 to block the NF-κB pathway, and exerted a positively regulatory role on HCV replication. CONCLUSION: miR-215 facilitated HCV replication via inactivation of the NF-κB pathway by inhibiting TRIM22, providing a novel potential target for HCV infection.